Math, asked by rohitdphilip, 1 year ago

the roots of quadratic equation x² - 5x + 6

Answers

Answered by aryan1234243
1

Step-by-step explanation:

x²-6x+x-6=0

x=6 and x=-1 is the answer of this question

Answered by Anonymous
1

 {\huge{\gray{\underline{\mathbb{\red{Ans}{\orange{wer}{\blue{:-} }}}}}}}

 {x}^{2}  - 5x + 6

 =  {x}^{2}  - 6x  -  1x + 6 \\  = x(x - 6) - 1(x  - 6) \\  = (x - 6)(x - 1)

1st zero

x - 6 = 0 \\ x = 6

2nd zero

x - 1 = 0 \\ x = 1

 {\mathbf{\red { | } {\red {\overline {\underline {\gray { \:brainliest\:if\: it \:helps \:you\:  }}}}}}}{\red{ | }}

{\orange{\fbox{\underline{\gray{\mathfrak{stay \:blessed}}}}}}

{\red{\fbox{\underline{\green{\tt{be \:happy}}}}}}

 {\red{\fbox{\gray{\fbox{\orange{\ddot{\smile}}}}}}}

Similar questions